Community Intervention in Sustainable Food Yard Program for Women Farmer Group in Tigo Koto Diate Village, Indonesia - Sinaga, Randa Putra Kasea; Adri, Intan Purnama (Journal of Peasants' Rights, 2023)
This research investigated how community interventions are implemented by the Food Security Agency through the Sustainable Food Yard Program for the Dahlia Sakato Women Farmer Group. This study describes the implementation of Community interventions in 12 variables using a qualitative approach.Â  Based on the results of the research and analysis performed to examine the community intervention model, it is possible to infer that this program is a type of intervention with the Capacity Development with Substantial Planning / Policy model. This is based on a program practice strategy that develops competencies through pre-planned actions. This study also suggests that future studies look at the program's long-term impact as an endeavor to establish food sovereignty.